META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS ON FINERENONE FOR CARDIOVASCULAR OUTCOMES IN TYPE 2 DIABETES AND CHRONIC KIDNEY DISEASE: META-ANALISIS UJI ACAK TERKONTROL FINERENON TERHADAP LUARAN KARDIOVASKULAR PADA DIABETES TIPE 2 DAN PENYAKIT GINJAL KRONIK - Khairuman Fitrah Ananda; Abigail Christine Sarumpaet; Agustina Sianturi (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Patients with chronic kidney disease and type 2 diabetes mellitus are at high risk for cardiovascular events. Finerenone, a non-steroidal mineralocorticoid receptor antagonist, shows potential as an additional therapy with cardioprotective effects. We conducted a meta-analysis based on data from randomized controlled trials by systematically searching the PubMed and ScienceDirect databases, using the PICOS framework: chronic kidney disease and type 2 diabetes mellitus (P); finerenone (I); placebo (C); cardiovascular outcomes (O); and randomized controlled trials (S). We included articles published within the last 10 years and available in full-text format. A total of 4 RCTs were included in this analysis. Statistical analysis was performed using the Random Effect Model. The analysis showed that finerenone reduced the odds of non-fatal myocardial infarction by 9% compared to placebo (OR 0.91; 95% CI: 0.80–1.03) and reduced the risk of hospitalization due to heart failure by 17% (OR 0.73; 95% CI: 0.66–0.82). All statistical results were significant, except for non-fatal myocardial infarction. The heterogeneity level was assessed as low to moderate (I² = 10%, 0%, and 58%). Risk of bias assessment using the RoB-2 tool indicated that all included studies had a low risk of bias. Finerenone demonstrated better outcomes compared to placebo, suggesting its potential benefit in improving cardiovascular outcomes in this population.